A prospective multi-site study to evaluate the performance and usability of an oral fluid-based HIV self-test in Canada - Richard A. Galli; Darshanand Maraj; Kristin McBain; Jason M. Lo Hog Tian; Abbey McFarland; Wangari Tharao; Nontobeko P. Nkala; Arlene Chan; Mark da Silva; Rejean Thomas; Anne-Fanny Vassal; Martin Lepage; et al. (BMC Public Health)
Abstract Background Blood and oral fluid-based HIV self-tests are important for reaching the undiagnosed living with HIV. The study objectives were to evaluate the oral fluid-based OraQuick® HIV Self-Test (HIV-ST) performance in comparison to laboratory reference testing; determine if laypersons can correctly perform the HIV-ST; document if intended users can successfully interpret pre-made contrived positive, negative, and invalid results; and document if intended users can understand the key messages in the product labeling. Methods This prospective study enrolled consenting adult intended users of HIV self-testing from six community health centres in four Canadian provinces between June 2022 and January 2024. Positive and negative agreement was determined by comparing the results of the HIV self-tests with the results of the laboratory-based “gold standard” Abbott Alinity HIV Antigen/Antibody Combo test. Descriptive statistics were used to summarize usability self-test procedure steps. Results Overall, 951 participants were recruited and consented with 911 available for all analyses. With respect to sociodemographics: 84% of participants were between 18–45 years of age, 73% had at least a college education, 48% were Cis-male, 45% were employed; and 26% identified as White, 23% as African, Caribbean or Black, 5% as Indigenous [First Nations, Métis or Inuit], 33% as Asian, and 6% as LatinX. Primary efficacy analysis on the 911 who completed HIV-ST revealed a single confirmed positive participant and a negative percent agreement of 100% (880/880, 95% CI: 99.9–100%) with the comparator method. For usability determination, the average success rate for “critical” steps for completing the test was 94.1%. Approximately 97% of participants found the instructions easy to follow and 98% of participants reported they would use the test again. Of the 465 participants who interpreted the strong positive, weak positive, negative, and invalid pre-made contrived results, the average of correct interpretations ranged from 59–97% Conclusions A licensed oral fluid-based HIV self-test in Canada can present an accurate, easy-to-use, and less invasive alternative to blood-based HIV testing. The addition of an oral-fluid self-test along with the current licensed blood-based HIV self-test could help reach the undiagnosed with HIV in Canada and positively impact HIV testing rates overall by offering individuals a choice of self-testing devices.